Microbial Biodiversity in Honey and Pollen Pots Produced by Tetragonisca angustula (Jataí) - Beux,Marcia Regina (2022)
Abstract The combination of nutritional and chemical factors in honey and pollen produced by Tetragonisca angustula (jataí) reveals a unique ecosystem that is conducive to developing microorganisms. However, there is a lack of information regarding the microbial species grown in the nest pots of this stingless bee species. The objectives of this study were to count, isolate and identify the microbiota associated with the pots of honey and pollen. The samples were collected from three jataí beehives. Microbiological analyses showed that the average total aerobic mesophiles ranged between 3.78 and 3.71 log CFU/g; lactic bacteria were 3.59 and 3.56 log CFU/g; and the yeast was 4.41 and 4.66 log CFU/g for the honey and pollen, respectively. There were four gram-positive cocci bacteria (Staphylococcus saprophyticus subsp. bovis, S. vitulinus, S. kloosii and S. pasteuri); two spore-forming gram-positive bacteria (Bacillus pumilus and B. thuringiensis); and one gram-negative bacteria (Pantoe agglomerans). One lactic bacteria (Leuconostoc mesenteroides subsp. mesenteroides) was also identified. Three yeast species were isolated (Starmerella meliponinorum, Candida magnoliae and Zygosaccharomyces bailli). Bacillus was the main bacteria in jataí honey and pollen. Z. bailli was the dominant yeast in the pollen, and S. meliponinorum was the dominant yeast in the honey. T. angustula bees and their products (honey and pollen) are ecosystems that provide sustainable environmental and technological integration. They also provide a selection of microorganisms that can be applied in the food, cosmetic and pharmaceutical industries.